Implications of Domains of Language Use and Attitude for the Implementation of the Magar Languages as Official Languages in Nepal - Regmi, Dan Raj; Regmi, Ambika (Nepalese Linguistics, 2022)
Language Commission has recommended the Magar language as official language in two provinces, viz. Gandaki and Karnali. However, implementation has been a Hercules task due to some extra-linguistic and linguistic problems. The languages spoken in the Magar community are not vibrantly used due to the weak ‘instrumental’ attitude. To implement the Magar languages as official languages some extra-linguistic strategies have to be executed. Moreover, effective linguistic strategies have to be framed to bring them to sustainable use.